IMPROVEMENT OF KNOWLEDGE AND CARING BEHAVIOR THROUGH E-LEARNING: DOI: https://doi.org/10.35654/ijnhs.v1i2.44 - Putri Nilasari; Rr. Tutik Sri Hariyati (International Journal of Nursing and Health Services (IJNHS), 2018)
Background: 4.0 industrial revolution raises new challenges for nurses to stay up to date on science knowledge by utilizing information technology advances. This is because science is the basis of nurses in making the best nursing care for patients. Methods: Literature review of 25 journals from Science Direct, PROQUEST, Scopus, and Scholar Article in 2014 to 2018. Results: Some results of the study show that the use of e-learning in providing education of nurses can increase knowledge to nurses' caring behavior in providing nursing care, and one of the e-learning devices in the hospital is a webinar. Conclusion: E-learning provides opportunities for nurses to gain knowledge through the use of electronic systems. One of the e-learning devices in the hospital that can be used as a reference when nurses want to study is webinar. Not only nurses who work at the hospital who can get benefits from webinar, but so do nurses in other health services. Although facilities and infrastructure are inadequate in an HR hospital, but nurses can intelligently use webinar as a source to gain knowledge.